The princess pact eaudiobook A twist on rumpelstiltskin. - Melanie Cellier (Four Kingdoms, 2020)
Spinning straw into gold was only the beginning of the story . . . Marie, the dutiful princess of Northhelm, chafes under the rigid protocol that governs her life. Then a growing darkness threatens the kingdom and uncovers the lie at the center of her whole life—a single pact that changes everything. Throwing off convention, she joins Rafe, a handsome, charming newcomer, on a quest to save her kingdom. Except he doesn't know she has a mission of her own—to discover the truth about her identity. Increasingly drawn to Rafe's strength and good humor, Marie is torn by her double purpose. With time running out and death and destruction looming, Marie will have to unravel the bargains that surround her and choose where her true allegiance lies. In this twist on the classic fairy tale, Rumpelstiltskin , a hidden identity is just one of the things Marie will have to unravel.